A Revolution for the Screen : Abel Gance's Napoleon - Cuff, Paul (Book collections on Project MUSE., 2015)
Abel Gance's silent masterpiece, 'Napoleon', was given a limited run on its debut in 1927, but soon afterwards distributors in France and America, unwilling to deal with its nine-hour running time, subjected it to savage cuts - with devastating results for the movie and for film history. The struggle across ensuing decades to restore and reintegrate Gance's film has formed a backdrop to an array of formal, contextual, and ideological battles. In this book, Paul Cuff takes account of those battles and challenges received opinion on Gance's view of both his film and its subject.--Back cover.